Assessment of waqf models for provision of affordable housing in Malaysia: a case study of Majlis Agama Islam Wilayah (MAIWP) - Bello, Hafis; Ayob, Mohd Fairullazi; Ahmad Sarkawi, Azila (Kulliyah of Architecture and Enviromental Design, 2020)
Housing is one of the basic needs of human beings. Despite its importance, housing prices have continued to increase beyond the reach of the masses. Realizing the fact, the government has made different attempts to ensure the provision of affordable and decent housing for the masses through many initiatives such as the enactment of the Perumahan Rakyat 1Malaysia Act 2012 (Act 739); implementation of My First Home Scheme and other and other social schemes, however, there is still a wide gap in the supply and demand for housing. Consequently, this study assessed the different Waqf financing models towards the provision of affordable Waqf housing in the country. Data were gathered from primary and secondary sources. Primary data was gathered through interviews with the Majlis Agama Islam Wilayah Persekutuan (MAIWP), while secondary data was gathered from the review of the literature. The findings indicate that MAIWP adopts the BOT (Built Operate and Transfer) model in its property development programme, and this model could help in the development of Waqf real estate. Despite operating in the most expensive city in the country, MAIWP has thus been able to provide affordable housing for the beneficiaries.